Diagnostic transitions from childhood to adolescence to early adulthood. (2nd March 2013) - Copeland, William E.; Adair, Carol E.; Smetanin, Paul; Stiff, David; Briante, Carla; Colman, Ian; Fergusson, David; Horwood, John; Poulton, Richie; Jane Costello, E.; Angold, Adrian
<x xml:space="preserve">Abstract</x> Background Quantifying diagnostic transitions across development is needed to estimate the long‐term burden of mental illness. This study estimated patterns of diagnostic transitions from childhood to adolescence and from adolescence to early adulthood. Methods Patterns of diagnostic transitions were estimated using data from three prospective, longitudinal studies involving close to 20, 000 observations of 3, 722 participants followed across multiple developmental periods covering ages 9–30. Common DSM psychiatric disorders were assessed in childhood (ages 9–12; two samples), adolescence (ages 13–18; three samples), and early adulthood (ages 19 to age 32; three samples) with structured psychiatric interviews and questionnaires. Results Having a disorder at an early period was associated with at least a threefold increase in odds for having a disorder at a later period. Homotypic and heterotypic transitions were observed for every disorder category. The strongest evidence of continuity was seen for behavioral disorders (particularly ADHD) with less evidence for emotional disorders such as depression and anxiety. Limited evidence was found in adjusted models for behavioral disorders predicting later emotional disorders. Adult substance disorders were preceded by behavioral disorders, but not anxiety or depression. Conclusions Having a disorder in childhood or adolescence is a potent risk factor for a range of psychiatric problems later in development. These findings provide further support for prevention and early life intervention efforts and suggest that treatment at younger ages, while justified in its own right, may also have potential to reduce the risk for disorders later in development.